EFFECT OF TEMPERATURE VARIATION ON QUALITY OF SPINAL ANAESTHESIA USING 0.5% BUPIVACAINE IN PATIENTS UNDERGOING CESAREAN SECTION - Safia Iqbal; Shumaila Motiwala; Sumreen Arif; Muneeba Arshad; Tooba Usman; Aftab Imtiaz (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Spinal anesthesia with intrathecal bupivacaine is widely used for cesarean sections. However, the temperature of bupivacaine may influence the onset, spread of sensory block, and incidence of shivering. Warming the anesthetic solution could enhance block characteristics and reduce perioperative discomfort.Objective: To compare the effects of room temperature versus warmed intrathecal bupivacaine on sensory block levels and shivering incidence in patients undergoing cesarean section under spinal anesthesia.Study Design & Setting: A randomized controlled trial conducted at Department of Anaesthesia, Abbasi Shaheed Hospital, Karachi from 14th June 2022 till 15th December 2022.Methods: A total of 142 parturients scheduled for elective cesarean section were randomly allocated into two groups: Group A received room temperature bupivacaine (n=71), and Group B received warmed bupivacaine (n=71). Sensory dermatomal levels were assessed, and the incidence of shivering was recorded intraoperatively. Statistical analysis compared the onset, extent of sensory block, and shivering frequency between groups.Results: The warmed bupivacaine group achieved higher sensory levels, with 21% and 61% of patients reaching T4 and T5 levels respectively, compared to 4% and 18% in the room temperature group. Shivering occurred less frequently in Group B (31%) compared to Group A (69%), though this difference did not reach statistical significance (p=0.111). The warmed group exhibited faster onset and better cephalad spread of sensory blockade.Conclusion: Warming intrathecal bupivacaine significantly improves sensory block characteristics and tends to reduce the incidence of shivering during cesarean sections under spinal anesthesia. These findings support the clinical advantage of warming bupivacaine to enhance anesthetic efficacy and patient comfort.